Hello, Dolly [videorecording (DVD)] - Kelly, Gene, 1912-1996; Streisand, Barbra; Matthau, Walter; Crawford, Michael, 1942-; Armstrong, Louis, 1901-1971; Stewart, Michael, 1929-1987; Wilder, Thornton, 1897-1975 (20th Century Fox Home Entertainment : Fox Video, 2003)
Musical set in the 1890's about a professional matchmaker who meets her match.